If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 4x = 9 Reorder the terms: 4x + 7y = 9 Solving 4x + 7y = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7y' to each side of the equation. 4x + 7y + -7y = 9 + -7y Combine like terms: 7y + -7y = 0 4x + 0 = 9 + -7y 4x = 9 + -7y Divide each side by '4'. x = 2.25 + -1.75y Simplifying x = 2.25 + -1.75y
| f+(vc)*q=(sp)*q | | 3/2+11/8+5 | | -4+5y/4=5/3 | | 8/2.8 | | -2(3x-10)=20 | | 1/5y-5=7 | | 6.35=7+x | | 2m-(m+10)=0 | | 4x-(x+1)=x-(x-5) | | 1/4=-x+8/5 | | 6+40=210 | | -1+8y/5=-5/3-y+3y/5 | | 9.5x+3=5.5x+4 | | (4/5)+(2/7)= | | 30z+(27z-5)=-28 | | 17/9= | | 17x-(5x-9)=21 | | -1+y/3=0 | | 3(x)-8=100 | | 6y+3x=15 | | 11y-12/8+3y/5=6y-1/8 | | (2x)^0/-2^4 | | 11+25y+29y=-14+27y-18y | | -5y/4+8/3=0 | | x+8y=38 | | (3r^2+10r-8)(12r^2-4r+3)= | | -9/4+3y+4=-9y-3 | | 2(2x-3)=3(x+6) | | 4(5x+3)=-5(x-2) | | 9k^2+5k+4=0 | | x^2+16x+105=0 | | x+4y=18 |